NEUROPATI PADA PENDERITA HIV - Paulus Sugianto* (Neurona Majalah Kedokteran Neuro Sains, 2011)
PURPOSE OF THIS ARTICLE IS TO ENHANCED OUR KNOWLEDGE IN DIAGNOSIS AND TREATMENT OF PERIPHERAL NEUROPATHIES IN HUMAN IMMUNODEFICIENCY VIRUS HIV PATIENTSPERIPHERAL NEUROPATHIES ARE COMMON IN HIV INFECTION SYMPTOMATIC NEUROPATHY OCCURS IN APPROXYMATELY 1015 OF HIV INFECTED PATIENTS OVERALL PERIPHERAL NEUROPATHIES ARE COMPLEX AND DIVERSE COMPLICATE ALL STAGES OF THE HIV DISEASE AND CAUSE CONSIDERABLE MORBIDITY AND DISABILITY IN HIVINFECTED INDIVIDUALS AND AIDS PATIENTS